Concentric and eccentric shoulder and elbow muscle strength in female volleyball players and non-active females - Alfredson, H.; Pietila, T.; Lorentzon, R. (Scandinavian Journal of Medicine & Science in Sports, 1998)
Maximal isokinetic concentric (60 degrees/s and 180 degrees/s) and eccentric (60 degrees/s) muscle strength of the external and internal rotator muscles of the shoulder and the flexor and extensor muscles of the elbow was measured in a position resembling spiking and serving in volleyball, on 11 non-injured female volleyball players (first division) and 11 non-active females. In the dominant arm, the volleyball players had significantly higher concentric peak torque of the internal and external rotators and elbow extensors at both velocities, and significantly higher eccentric peak torque of the shoulder internal and external rotators and elbow flexors and extensors, than the controls. In the volleyball group, the concentric internal rotation peak torque at 60 degrees/s was significantly higher in the dominant than in the non-dominant arm. The external/internal strength ratio was significantly lower at 60 degrees/s, but not at 180 degrees/s, in the dominant arm. CONCLUSION: The female volleyball players had a higher concentric and eccentric strength in the rotator muscles of the shoulder and in the extensor muscles of the elbow compared to untrained controls in this special test position. There were signs of rotator muscle imbalance at the low test speed, but no signs of weakness of the external rotators, in the dominant arm of the volleyball players.